Enhancing DSSC Performance through Metal-Doped TiO₂ and Poly-Tannin Dye: A Study on Bandgap Reduction and Photon Absorption - Hardeli, Hardeli; Ade Putri, Anisa; Gusmar Lina, Resi; Feronika, Widi; Permatasari, Putri (P3M Politeknik Negeri Jember, 2025)
Dye-sensitized solar cells (DSSC) are a promising alternative to conventional solar cells by using dye molecules to absorb sunlight and facilitate energy conversion. In this study, tannins were used as the dye. Tannins can be polymerized into poly-tannins, which increases the amount of double bonds and therefore improves photon absorption. Furthermore, this study will also examine how metal doping affects the TiO₂ semiconductor to further enhance its performance. The selected dopants—Cu, Fe, and Ag—were tested for their capacity to change the bandgap and increase electron mobility. Experiments showed that metal doping lowered the bandgap of TiO₂, resulting in better electron excitation and charge transfer. Under optimum conditions, the combination of poly-tannin dye and TiO₂-Ag semiconductor resulted in the highest DSSC efficiency (9.18%). Based on this, it can be concluded that combining metal-doped TiO₂ with poly-tannin dyes can greatly improve DSSC performance.